The Development of E-Modules of Pancasila Education Learning with the Flipbook Application - Sakinah, Gita Sari; Indrawadi, Junaidi; Suryanef, Suryanef; Ernawati, Ernawati (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
The paper aims to develop an e-module for learning Pancasila education using the flipbook application at SMP Negeri 6 Bukittinggi that is valid, practical, and effective. This type of research is development research with a 4D development model design, namely define, design, develop, and disseminate. The population in this research is class VII of SMP Negeri 6 Bukittinggi, and the sample is 30 students. The instruments used in this development are validation sheets, e-module practicality test sheets, and effectiveness sheets, while the data collection techniques used in this e-module development research use three types of data collection techniques, namely through interviews, questionnaires, and tests. This research uses two types of data, namely quantitative and qualitative. Quantitative data is data in the form of material, media, and language expert validation sheets. The data and data sources used in this research are primary and secondary data sources. Primary data was obtained directly from the source, namely by observing the implementation of learning and conducting interviews with teachers and students. Secondary data used are written sources, such as books, documents, and journals related to research. The data analysis technique in this research is testing the validity, practicality, and effectiveness obtained through the instruments that have been developed. The results of validation by media experts obtained an average score of 83%, material experts obtained an average score of 92%, and language experts obtained an average score of 98%. For practical results by teachers, the average was 92%, while for the effectiveness of teaching materials, it was 3.77. From the results of this research, it can be concluded that the use of the Pancasila education learning e-module with the flipbook application is suitable for use in the learning process.